Optimisation of user-selectable volumetric modulated arc therapy (VMAT) planning parameters: A study of VMAT arcs for prostate and head-and-neck cancers - Ghulam Murtaza; Zaheer Abbas Gillani; Shahid Mehmood; Jalil Ur Rehman; Ehsan Ullah Khan (Journal of the Pakistan Medical Association, 2021)
Objective: To evaluate different VMAT planning techniques for a multi-leaf collimator (MLC)providing maximum aperture of 21 × 16 cm². Methods: A VMAT planning study of nine prostate and nine head-and-neck cancer patients was carried out. The patients were previously treated with Intensity Modulated Radiotherapy (IMRT) technique during 2014-15, at radiation oncology SanBortolo Hospital, Vicenza, Italy. Three VMAT plans for each of prostate and head-and-neck cancer patient were optimized using Pinnacle treatment planning system for 6MV photon beam from ElektaSynergyS®Linac system. Single arc, dual arc and combined two independent-single-arcs were optimized for collimator angle 45°. VMAT treatment planning comparison was made among single-arc dual-arc and combined two independent-single-arcs. The student’s t-test (two-sided) with p ? 0.05 was applied for significant difference between dose volume indices of plans. Results: All VMAT techniques produced clinically acceptable plans for prostate, while for head-and-neck, DA and ISAs significantly improved target coverage compared to SA. Single arc is sufficient for prostate, while inefficient in case of head-and-neck dose-planning. In spite of having different VMAT optimization approach dual arc and two combined independent-single-arcs provided very similar target coverage, while dual arc improved sparing of organs-at-risk. Similar treatment delivery times were observed for DA and ISAs VMAT techniques. Conclusion: Single arc is sufficient for prostate, while inefficient in case of head-and-neck dose-planning.Dual arc and two combined independent-single-arcs provided similar PTV coverage, while DA provided better sparing of organs at risk. Continuous...